2019
DOI: 10.3354/esr00983
|View full text |Cite
|
Sign up to set email alerts
|

Riverscape correlates for distribution of threatened spotfin chub Erimonax monachus in the Tennessee River Basin, USA

Abstract: Globally, aquatic biodiversity is imperiled at an increasing rate, especially in diversity hotspots such as the southeastern USA. The spotfin chub Erimonax monachus is a federally threatened minnow with a disjunct distribution resulting from numerous impoundments on the Tennessee River and its tributaries in the heart of the southeastern USA. Recovery actions required to remove federal protection for E. monachus are dependent on the establishment of additional populations within the historical range of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…Finally, our results revealed that the highest suitability of Prairie Chub was among large stream fragments with high densities of downstream dams (DMD; Cooper et al 2017). This pattern is consistent with the federally listed Spotfin Chub Erimonax monachus that is essentially isolated upstream of large reservoirs (Perkin et al 2019a) and highlights the lack of downstream connectivity that has already contributed to the decline and extirpation of Prairie Chub (Winston et al 1991).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, our results revealed that the highest suitability of Prairie Chub was among large stream fragments with high densities of downstream dams (DMD; Cooper et al 2017). This pattern is consistent with the federally listed Spotfin Chub Erimonax monachus that is essentially isolated upstream of large reservoirs (Perkin et al 2019a) and highlights the lack of downstream connectivity that has already contributed to the decline and extirpation of Prairie Chub (Winston et al 1991).…”
Section: Discussionsupporting
confidence: 75%
“…The local scale is the area of land draining immediately into an interconfluence stream segment, excluding all upstream segments, whereas the network scale includes the focal segment plus all upstream segments (Hill et al 2017). These two scales have been used in ENMs for freshwater fishes in other studies (Perkin et al 2019a) based on the medium-resolution NHD stream identification code (i.e., COMID), which allows for precise mapping of species distributions. Land use and land cover data included attributes such as agriculture, urbanization, and forested land covers, as well as cumulative habitat disturbance assigned to NHD stream segments by Daniel et al (2019).…”
Section: Abiotic Dimensionmentioning
confidence: 99%
“…Segments with both Headwater catfish and Channel catfish were denoted as presence locations (class = 1). The TGA method is commonly used in stream fish species distribution modelling implemented with presence–absence model algorithms (Huang & Frimpong, 2015; Malone et al., 2018; Perkin et al., 2019).…”
Section: Methodsmentioning
confidence: 99%